Guidelines for laboratory works on the topic "Industrial noise study" - Mezentseva, Irina Oleksandrivna; Ilinska, O. I.; Movmyga, N. E. (My University, 2022)
Guidelines for laboratory works are intended for practical work from the course "Fundamentals of Occupational Safety and Health" of the first (bachelor's) level of training for students of higher education in the specialties of the NTU KhPI. It is well known that noise adversely affects the human body. Workers who deal with noisy machines and mechanisms develop permanent hearing impairment, which often leads to occupational diseases. The long-term effect of noise on the human body leads to the development of chronic overfatigue, impaired thermoregulation, and the appearance of such symptoms as poor sleep, drowsiness, and impaired thermoregulation. All this can cause an accident at work. Noise affects the digestive and circulatory systems, the cardiovascular and endocrine systems, the nervous system, etc. Noise not only worsens a person's well-being, but also reduces work productivity by 10-15%. In this regard, the fight against it is not only of sanitary and hygienic importance, but also of great technical and economic importance. Industrial noise is one of the main harmful factors that causes occupational sensorineural deafness in workers of various professional groups. In the structure of occupational diseases in Ukraine, hearing diseases occupy the third place - 14.9% of the total number of diagnoses. Machine-building enterprises are one of the powerful sources of noise pollution. The purpose of these methodological instructions is for students to acquire the skills to independently solve an engineering problem: development of acoustic means of protection against noise in production, selection of the optimal option; determining the effectiveness of noise reduction measures at workplaces, taking into account the characteristics of noise sources and the peculiarities of their location in the room, etc. The goal of the work "Industrial noise study" is to assimilate the ways of constant noise rationing, experimental study and calculation of sound level (the sound pressure) from several sources, as well as sound isolation properties of a wall partition.
Keywords: guidelines; industrial noise; occupational safety and health; machine-building enterprises; development of acoustic means; the sound pressure